2020
DOI: 10.1080/21683565.2020.1822980
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and barriers in diversified farming and the use of agroecological principles in the Global North – The experiences of Danish biodynamic farmers

Abstract: Diversification through agroecological principles may maintain and stabilize yields in an increasingly more unpredictable climate, including market price fluctuations, as well as preserve and enhance the threatened natural resource base and the environment. Based on a participatory interview process this article identifies the barriers encountered by a group of Danish biodynamic farmers striving for self-sufficient farm systems with no or very little dependency on imported materials by developing biologically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…A large-scale monoculture agriculture system has deeply entrenched across the world ensuing difficulty for any alternative production system such as diversified farming to flourish [154,155]. Reluctance among the commercial farmers in adopting crop diversification could be because of not prioritizing the importance of ecology or the lack of knowledge about diverse farming models and relevant scientific mechanisms governing their several advantages [34,156]. In the absence of proper knowledge and skills, it is evident for the farmers to be more doubtful of the economic success of relatively complex farming systems on a large-scale.…”
Section: Major Constraints To Adoption Of Crop Diversification In Modern Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…A large-scale monoculture agriculture system has deeply entrenched across the world ensuing difficulty for any alternative production system such as diversified farming to flourish [154,155]. Reluctance among the commercial farmers in adopting crop diversification could be because of not prioritizing the importance of ecology or the lack of knowledge about diverse farming models and relevant scientific mechanisms governing their several advantages [34,156]. In the absence of proper knowledge and skills, it is evident for the farmers to be more doubtful of the economic success of relatively complex farming systems on a large-scale.…”
Section: Major Constraints To Adoption Of Crop Diversification In Modern Agriculturementioning
confidence: 99%
“…Although diversified farming uses agricultural inputs more judiciously and could be cheaper in the long run, small-scale farmers may struggle to establish a diverse agriculture farm as it requires more resources at the beginning. A case study on danish farmers revealed that, with the diversified cropping system, farmers experienced an increase in the types of farm activities, requiring broad knowledge, skills, equipment, manpower, and advisory services to run, and needing more years to return the initial investments [156]. Therefore, farmers with no other alternative income source are unlikely to take risk towards the diversified approach [154].…”
Section: Major Constraints To Adoption Of Crop Diversification In Modern Agriculturementioning
confidence: 99%
“…Not having proper policies and channels to disseminate farmer's knowledge to the extension workers and researchers also hinders the adoption of crop diversification. Inadequate legislation provisions to meet the needs of diversified farming are also reported by Aare et al [134] in Denmark. More restrictions were found regarding the use of certain species or cultivars, thus discouraging diversification.…”
Section: Major Constraints To Adoption Of Crop Diversification In Modern Agriculturementioning
confidence: 81%
“…A large-scale monoculture agriculture system has deeply entrenched across the world ensuing difficulty for any alternative production system like diversified farming to flourish [132,133]. Reluctance among the commercial farmers in adopting crop diversification could be because of not prioritizing the importance of ecology or the lack of knowledge about diverse farming models and relevant scientific mechanisms governing their several advantages [134,34]. In the absence of proper knowledge and skills, it is evident for the farmers to be more doubtful of the economic success of relatively complex farming systems on a large-scale.…”
Section: Major Constraints To Adoption Of Crop Diversification In Modern Agriculturementioning
confidence: 99%
See 1 more Smart Citation